ETUDE ANTHROPOLOGIQUE ET COMPARATIVE DES MANDIBULES HUMAINES DE LA CITE DES PIERRES (MOYEN ATLAS) A CELLES DE TAFORALT - khadou, Benlamine Lalla; Mohammed, Benabdelhadi; Aicha, Oujaa; Lahcen, Gourari; Michel, Fontugne (European Scientific Journal, ESJ, 2015)
The CPSI funeral monument is located In the North-West of the Middle Atlas, in the region of Adar Ouawine, approximately ten kilometres away from the town of Boulmane. It is a sandstone slab with an internal cavity in a scree zone that gave way to the remains of three individuals, one man and two women. They are buried in a lateral decubitus positions. The orientation of their body is North-South, the heads towards the North. The three mandibles exhumed are complete and in a very good state of conservation. The origin of the builders of the funeral monuments of North Africa in the protohistoric periods is debated. The results of the historic searches, ethnologic and linguistic on the subject oppose two theses. Gabriel Camps’s defends an oriental origin of the Protomediterranneans, assuming a progressive replacement of the existing local population and of other researchers who support the idea of a local anthropologic evolution of the Iberomaurusian population. We have based our approach on an anthropologic, as morphologic as morphometric and statistic, of the physic characteristics of the human remains found in the CPSI monument to define and compare them to the morphotype of Taforalt known to represent the Iberomaurusian population of Morocco. The morphometric and the statistical analysis of these mandibles showed that they presented physical characteristics consistent with the mandibles of the Men of Taforalt, particularly with H1’s mandible. The ACP showed that the CPSI and Taforalt individuals belong to two different populations. This distinction is explained by the slenderisation of the CPSI individuals who nevertheless keep morphological characteristics specific to the Mechta type. The morphological fit and the slenderisation allow us to establish a possible filiation between Berber populations, builders of the monuments of the Middle Atlas, and the oriental Moroccans in Taforal. This acknowledgment supports the thesis of local anthropological evolution during the protohistoric periods and weakens the thesis of the oriental origin of the Protomediterraneans.